Atmospheric emission of mercury due to combustion of steam coal and domestic coal in China. (August 2017) - Wang, Shaobin; Luo, Kunli
Abstract: To study the mercury emission due to the combustion of steam coal and domestic coal in China, we analyzed the mercury contents of coal, fly ash, bottom ash and sluicing water in thermal power plants, steam boilers as well as domestic coal-stoves, in Shaanxi, Shanxi, Shandong and Yunnan Provinces. This study conduct an estimate of the Hg emission rates from steam coal and domestic coal combustion based on the method of mass distribution ratio of fly ash and bottom ash. The results show that the Hg emission rate of coal combustion in thermal power plants is about 50.21% (electrostatic precipitators + wet flue gas desulfurization), and that in heating boilers is about 67.23%, and 92.28% in industrial boilers without flue gas desulphurisation equipment. Furthermore, Hg emission rate is 83.61% due to domestic coal combustion in coal-stoves. The Hg emission amount into the atmosphere from power and heat generation, industrial boilers, domestic coal-stoves and spontaneous combustion of coal gangue is roughly estimated to be 133 ± 4, 100 ± 17, 11 ± 0.1 and 47 ± 26 tons in China in 2014, respectively, and the total Hg emission amount from this paper is estimated at 292 tons. The trends of Hg emission in China from 1991 to 2014 show an accelerating growth after 2002. The proportion of mercury emission due to thermal power, heating generation and industrial energy utilization continuously increased. The atmospheric emission of mercury due to combustion of steam coal, domestic coal and coal gangue accounts nearly 50% in total anthropogenic Hg emissions in China, indicating one of the largest sources of Hg emission in China which should draw more public and scientific attention in the future. Highlights: We quantified Hg emission rates from steam coal, domestic coal combustion and coal gangue. Hg emission into the atmosphere is estimated to be 292 tons in China in 2014. The trend of Hg emission shows an accelerating growth after 2002. Hg emission due to coal utilization and coal gangue should draw more attention in the future.